Yavnykh proyaviv nemaye - Gorlova, Alina (Ukraine, 2018)
This film documents a story of the woman who returns from war. Talking to psychologists, battling her PTSD and panic attacks, she tries hard to get back to normal life. The documentary shows her path from the beginning of her rehabilitation till her going back to work.
Verzio Film Festival Submission
Keywords: Documentary films